OP115 Expanding Perspectives: The Role Of Environmental Scanning In Health Technology Assessment. (2019) - Pollock, Michelle; Guo, Bing
Abstract : Introduction: Environmental scan reports, usually consisting of literature reviews and/or key informant consultations (such as online surveys or personal interviews), broadly describe the current local, national, and international landscape surrounding health care practices, programs, or the use of technologies. Funding agencies and health organizations recognize environmental scans as a valuable way to inform decision-makers about the context, practice variations, and knowledge gaps surrounding a topic. Despite their increasing popularity in health technology assessment (HTA), there is limited guidance available for conducting environmental scans, variation in methods used across and within HTA agencies, and lack of consensus on an appropriate definition, purpose, and process. Methods: We conducted an informal literature review and consulted experienced researchers from other HTA agencies to identify existing methods guidance for conducting environmental scans. We then adapted these methods to conduct an environmental scan of initiatives to accelerate cancer diagnosis. Results: There was limited and vague guidance on the definition, purpose, and process of conducting environmental scans in the context of HTA. This introduced challenges but provided the flexibility to modify our approach to meet requestor needs. Our environmental scan included: (i) a literature review, to identify and describe relevant initiatives and to locate data on effectiveness (which is often out-of-scope for environmental scans but was of priority to the requestor); (ii) stakeholder surveys, which helped "fill in the gaps" of the literature review and helped locate additional initiatives; and (iii) targeted key informant interviews, which provided rich follow-up data on the initiatives most important to the requestor. Conclusions: By describing our experiences adapting limited methods guidance to meet requestor needs, we hope to contribute to the evolving discussion about the definition, purpose, and process of environmental scans to inform health policy decision-making. We will reflect on challenges encountered, potential solutions, and lessons learned, and will discuss ongoing areas of methodological uncertainty.